Effect of Cross‐Link Density on Carbon Dioxide Separation in Polydimethylsiloxane‐Norbornene Membranes. Issue 21 (2nd November 2015) - Hong, Tao; Niu, Zhenbin; Hu, Xunxiang; Gmernicki, Kevin; Cheng, Shiwang; Fan, Fei; Johnson, J. Casey; Hong, Eunice; Mahurin, Shannon; Jiang, De‐en; Long, Brian; Mays, Jimmy; et al.
Abstract: Invited for this month′s cover is the team of researchers at Oak Ridge National Laboratory and several research groups at the University of Tennessee, Knoxville. The image shows the use of cross‐linked polydimethylsiloxane–norbornene membranes to separate CO2 from flue gas. The Full Paper itself is available at10.1002/cssc.201500903 . Abstract : "Since the membrane separation could offer a great reduction in energy cost…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at10.1002/cssc.201500903 . View the Front Cover here:10.1002/cssc.201501420 .